1999
DOI: 10.1180/claymin.1999.034.3.10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clay Minerals and Exchangeable Cations on the Formation of Humic-Like Substances (Melanoidins) from D-glucose and L-tyrosine

Abstract: The ability to produce humic-like polymeric compounds, with D-glucose and L-tyrosine as starting materials, was evaluated in different mineral systems: (1) Ca-, A1-and Cu(II)-saturated montmorillonite; (2) Ca-, A1-and Cu(II)-saturated kaolinite; (3) quartz in the presence of two different amounts of the same cations (according to the cation exchange capacity of the clays); and (4) untreated quartz (as control). All systems proved to be effective in the formation of humic-like compounds, particularly quartz, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…While the Maillard reaction is well known in medicine and nutrition (Ikan 1996), the extent to which it can stabilize or protect proteins in soils has not been studied. Previously considered to require too extreme a temperature to occur extensively in soils (Arfaioli et al 1999;Bosetto et al 2002), recent in vitro work has shown that, at least for free amino acids, the Maillard reaction can be catalyzed by clays (Arfaioli et al 1999;Bosotto et al, 2002), common minerals (Jokic et al 2001) and polyphenols (Jokic et al 2004). Maillard products occur extensively in soil char, however (review by Knicker (2006, this volume).…”
Section: Carbohydratesmentioning
confidence: 96%
“…While the Maillard reaction is well known in medicine and nutrition (Ikan 1996), the extent to which it can stabilize or protect proteins in soils has not been studied. Previously considered to require too extreme a temperature to occur extensively in soils (Arfaioli et al 1999;Bosetto et al 2002), recent in vitro work has shown that, at least for free amino acids, the Maillard reaction can be catalyzed by clays (Arfaioli et al 1999;Bosotto et al, 2002), common minerals (Jokic et al 2001) and polyphenols (Jokic et al 2004). Maillard products occur extensively in soil char, however (review by Knicker (2006, this volume).…”
Section: Carbohydratesmentioning
confidence: 96%
“…These dark colored substances may be complex, insoluble, and nonhydrolysable polymers called melanoidins. Melanoidins are N-rich, humic-like products of the Maillard reaction formed from the condensation of amino acids and reducing sugars with an affinity for clay mineral surfaces (Arfaioli et al 1999(Arfaioli et al , 2003Derenne and Largeau 2001;Hedges 1978). Presence of these dark-colored substances formed during extraction may bias the results of the colorimetric Bradford assay and result in an overestimation of soil protein when tannins are present.…”
Section: Effects Of Tanninmentioning
confidence: 97%
“…Condensation of glucose and tyrosine/glycine/ tryptophan at 70 ° C: FTIR spectra resembling natural humic substances; yields of humic substances; XRD investigation into change in d -spacings Arafaioli et al (1997Arafaioli et al ( , 1999 ; Bosetto et al (1995Bosetto et al ( , 1997Bosetto et al ( , 2002 Smectites Condensation of arginine and glucose at 37 ° C; C and N fractions yields; FTIR spectra of solid residue and supernatant humic substances; XRD investigation into change in d -spacings Gonzalez and Laird (2004) …”
Section: Clay -Size Layer Silicatesmentioning
confidence: 99%